Strategi Peer Educator untuk Peningkatan Kesadaran Pekerja Seks Perempuan terhadap Kesehatan Reproduksi - Lidya Febrina (Jurnal Sosiologi Andalas, 2020)
This article presents the results of research on peer educator strategies to raise female sex workers' awareness of reproductive health. The objectives of this study were 1) to describe the strategies used by peer educators to build sex worker awareness of workers' reproductive health; 2) Identifying barriers to peer educators in providing education on reproductive health to female sex workers. To achieve the research objectives, the theory used is the Social Exchange Theory of George C, Homans and the research approach used is qualitative with descriptive research type. To obtain data, researchers used in-depth interviews and observation techniques. The results showe that the strategies used by peer educators in providing education about reproductive health were: coercion, giving advice, and persuasion. Meanwhile, the obstacles found by peer educators in providing education on reproductive health were: the imbalance of exchanges between peer educators and female sex workers and the distrust of female sex workers in peer educators.